Validity and Reliability of a Lithuanian Physical Education Teachers’ Self-Efficacy Scale Toward Inclusion of Students with Autism Spectrum Disorders (Baltic Journal of Sport and Health Sciences, 2018)
Background. Teacher’s perceptions of Self-efcacy (SE) have been suggested as an important factor in the successful inclusion of students with special educational needs. The purposes of this study were (a) to investigate the validity and reliability of the instrument of physical education teachers’ self-efcacy toward the inclusion of students with Autism Spectrum Disorders (PESEISD-A), using a Lithuanian physical education (PE) teachers’ sample, and (b) to assess relationships between SE scale and subscales. Methods. The English version of the instrument was translated into Lithuanian using the back-translation technique. The participants were 368 PE teachers working in Lithuanian schools (152 males and 216 females), aged between 24 and 65 years (M = 47.09; SD = 9.06). The content and construct validity of the instrument were supported. Results. The results of the factor analysis indicated a one-factor solution for the scale’s SE. Cronbach’s alpha reliability of SE scale and all other subscales was high (α > .93). Test-retest correlation analysis showed a satisfactory coefcient. In this study, positive and signifcant relationships between SE scale, mastery experience, vicarious experience, social persuasion, physiological state, behaviour, and perceived challenges subscales were determined (p < .01). Conclusions. The Lithuanian version of the PESEISD-A appears to be a valid and reliable instrument, enabling future research on Lithuanian PE teachers.Keywords: professional development, special education needs, self-efcacy theory, source of self-efcacy.